Assessing Interpersonal Proximity Evaluation in the COVID-19 Era: Evidence From the Affective Priming Task - Scerrati, Elisa; D'Ascenzo, Stefania; Nicoletti, Roberto; Villani, Caterina; Lugli, Luisa (Frontiers in Psychology, 2022)
Social proximity has since ever been evaluated as positive. However, the outbreak of the Covid-19 pandemic has dramatically reduced our social relations to avoid spreading the contagion. The present study aims at investigating people current assessment of social proximity by using an affective priming paradigm. We hypothesized that if our evaluation of social proximity is positive then words with a positive valence (e.g., relaxed) should be processed faster when preceded by images of social proximity than social distancing. On the contrary, if our evaluation of social proximity is turning to negative then words with a negative valence (e.g., sad) should be processed faster when preceded by images of social proximity than social distancing. To this end, we presented participants with prime images showing line drawings representing humans in situations of proximity or distancing and asked them to evaluate the valence (i.e., positive, negative) of a subsequent target word. In a follow-up session the same participants evaluated the prime images as being positively or negatively valenced. Results showed that a large subset of participants who rated the prime images of social proximity as positive also processed positive words faster when these were preceded by images of social proximity than social distancing. Conversely, a smaller subset of participants who rated the prime images of social proximity as less positive processed negative words faster when these were preceded by images of social proximity than social distancing. These results suggest individual differences in the assessment of social proximity likely driven by the pandemic.